2013
DOI: 10.1039/c3cc47174h
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed ortho-halogenation of protected anilines

Abstract: A practical Cu-catalyzed direct ortho-halogenation of anilines under aerobic conditions has been developed. The reaction shows typically excellent mono-substitution selectivity, high ortho-regiocontrol and large functional group tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(35 citation statements)
references
References 47 publications
0
35
0
Order By: Relevance
“…[47] In their process,ascreening of protecting groups revealed that the NH(SO 2 Py) group was uniquely effective for the high monoselectivity andr egioselectivity. This method uses convenient halogen sources, N-halosuccinimides (NXS,X= Cl, Br), providing an interesting procedure for the formation of ortho-Cl and ortho-Br aniline derivatives.…”
Section: C à Pb Ond Formationmentioning
confidence: 99%
“…[47] In their process,ascreening of protecting groups revealed that the NH(SO 2 Py) group was uniquely effective for the high monoselectivity andr egioselectivity. This method uses convenient halogen sources, N-halosuccinimides (NXS,X= Cl, Br), providing an interesting procedure for the formation of ortho-Cl and ortho-Br aniline derivatives.…”
Section: C à Pb Ond Formationmentioning
confidence: 99%
“…67 Ortho-mono-halogenation of anilines could be achieved with CuX 2 -NXS (X = Cl, Br)system. The one-step removal of the 2-pyridylsulfonyl auxiliary under mild reductive conditions afforded the free primary amine in high yield.…”
Section: Carbon-halogen Bond Formationmentioning
confidence: 99%
“…Inspired by the report on copper‐catalyzed functionalization of C(sp 2 )H bonds by the group of Yu,3 Daugulis and co‐workers reported the first example of copper‐promoted bidentate ligand‐directed CH functionalization reactions on sp 2 carbons in 2012: the sulfenylation of benzoic acid and benzylamine derivatives 4. Following this discovery, copper‐catalyzed direct amination,5 amidation,5b arylation,6 chlorination,7 etherification,8 and fluorination9 of arenes were rapidly established. Mechanistically, either an organometallic CH activation/functionalization or a single‐electron‐transfer pathway is believed to be involved in the process 5b.…”
Section: Optimization Of Reaction Conditions[a]mentioning
confidence: 99%